Farm Animal Enclosure Requirements, Industry Concentration, and Supply Chain Dynamics - Scheitrum, Daniel P.; Schaefer, K. Aleks (Frontiers in Animal Science, 2021)
In this paper, we draw on microeconomic theory to show that farm animal enclosure regulations can and have lead to increased farm-level concentration in affected industries in the U.S. The desirability of this increased concentration is a function of modern industry structures. Farm animal enclosure requirements can push traditional "short" supply chains like eggs toward vertical integration. However, vertically integrated systems (e.g., broiler chickens and hogs) may benefit from the induced farm-level concentration by increasing bargaining power among contract farmers. In all systems, the increased farm-level concentration induced by enclosure requirements may lead to greater ability to solve future collective action problems like wastewater pollution and antimicrobial resistance.